Seasonal variation of equatorial wave momentum fluxes at Gadanki (13.5° N, 79.2° E) - M. N. Sasi; V. Deepa (Annales Geophysicae, 2001)
The vertical flux of the horizontal momentum associated with the equatorial Kelvin and Rossby-gravity waves are estimated from the winds measured by the Indian MST radar located at Gadanki (13.5° N, 79.2° E) during September 1995 to August 1996 in the tropospheric and lower stratospheric regions for all four seasons. The present study shows that momentum flux values are greater during equinox seasons than solstices, with values near the tropopause level being  16 × 10-3, 7.4 × 10-3, 27 × 10-3 and 5.5 × 10-3 m2 s-2 for Kelvin waves and 5.5 × 10-3, 3.5 × 10-3, 6.7 × 10-3 and 2.1 × 10-3 m2